Open repair with latissimus muscle flap coverage for treatment of infected thoracic endovascular aneurysm repair - Lucas Ribé Bernal, MD; Rana O. Afifi, MD; Anthony L. Estrera, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2024)
A male patient, 70 years of age, was evaluated for an infected thoracic endovascular aneurysm repair (TEVAR). After presenting with persistent fever, a positron emission tomography scan found an infected aortic stent graft. The patient underwent open repair with explantation of the infected TEVAR, extensive periaortic debridement, graft replacement with a Dacron graft, and complete coverage with a latissimus dorsi muscle flap. Tissue culture revealed Clostridium spp. He was discharged home with long-term ampicillin and sulbactam. A postoperative computed tomography scan showed no recurrence of infection. Open surgery with latissimus muscle flap coverage is an achievable option for infected TEVAR.